2022
DOI: 10.1186/s13052-022-01217-6
|View full text |Cite
|
Sign up to set email alerts
|

Core self-evaluation, mental health and mobile phone dependence in Chinese high school students: why should we care

Abstract: Background Mobile phone dependence is a common problem in the population of high school students. We aimed to evaluate the core self-evaluation, mental health and mobile phone dependence in Chinese high school students, to provide reliable evidence to the support of high school students. Methods We conducted a survey of high school students in Xiamen, China. The self-assessment questionnaire on mobile phone use dependence among teenagers (SQAPMPU),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
2
8
1
Order By: Relevance
“…There is no significant difference in the mental health of senior high school students of all three grades. This discovery is slightly different from the findings of Li et al [ 25 ]. The parents of the students experienced the 2008 Wenchuan Earthquake.…”
Section: Discussioncontrasting
confidence: 99%
“…There is no significant difference in the mental health of senior high school students of all three grades. This discovery is slightly different from the findings of Li et al [ 25 ]. The parents of the students experienced the 2008 Wenchuan Earthquake.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, the findings suggested that depression and anxiety played a mediating role in the DBTP effect on mobile phone addiction, which was in line with previous research that mental health worsens when DBTP increases ( Oyanadel and Buela-Casal, 2014 ), which for adolescents tends to lead to higher mobile phone addiction ( Li et al, 2022 ). The COVID-19 pandemic resulted in an increase in mental health issues, such as anxiety, depression ( Shanafelt et al, 2020 ), panic, and other negative emotions ( Hagerty and Williams, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…The method calculates the difference between the actual and ideal scores on the five dimensions, squares the five differences and adds them together, and then finally squares the sum of the squares for the five differences. The optimal critical value was also revised to fit the Chinese version of ZTPI as reported in Jankowski et al (2020) , Li et al (2022) and Li and Lv (2022) the higher the DBTP, the more unbalanced the DBTP.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of emotional stability in the core self-evaluation, students with higher emotional stability tend to maintain a positive and optimistic emotional attitude in the face of academic stress, and are less likely to fall into an emotional trough, which helps to stabilize their psychological state. Students with strong self-control can better manage their emotions and learning strategies, thus reducing academic stress (Li et al, 2022 ). Meanwhile, individuals with stronger adaptive ability can more flexibly cope with different academic challenges and changes, and are less likely to experience excessive emotional fluctuations due to stress.…”
Section: Introductionmentioning
confidence: 99%